Assessing and strengthening community‐based coastal governance - Mark Andrachuk; Graham Epstein; Shauna Mahajan; Zephania Arnold; Sinezio Junior; Dresy Lovasoa; Monalisa Mabandla; George W. Maina; Caroline Njeri; Samson Obiene; Geoffrey Odhiambo; Lenice Ojwang; et al. (Conservation Biology, 2026)
Community‐based coastal governance is essential for biodiversity conservation and sustainable livelihoods, yet many communities continue to face significant challenges in establishing and sustaining effective governance systems. We sought to improve understanding of the current status of community‐based coastal governance across five countries in the Southwest Indian Ocean (SWIO) region of Africa. Using the Elinor tool and data system, we examined how specific governance attributes relate to perceived social and ecological outcomes and sought insights for community‐managed areas (CMAs) in the SWIO region. Progress toward strong community‐based governance of CMAs has been uneven across the region and across governance attributes. Although some CMAs have established clearly defined management boundaries and property rights, many other CMAs are still working to improve some attributes, such as congruent regulations, transparency, accountability, and operational capacity. Perceived ecological and social outcomes correlated with different governance attributes. Perceived ecological outcomes were positively correlated with measures of property rights and local governance, whereas perceived social outcomes were correlated with local governance and operational capacity. The strength of CMA governance tended to improve in the first 5–10 years after establishment, then governance attributes plateaued or declined thereafter. These findings coincide with typical funding cycles, thus reinforcing the value of continued investment in community‐based coastal governance. Specifically, our findings point to the importance of providing long‐term capacity development and securing durable conservation finance to ensure the success of CMAs. More broadly, these findings contribute to a growing body of evidence of the importance of paying attention to when and how to leverage different types of support and capacity building.

Overview of the WIO-Benth Project – benthic habitats and megafauna from soft sediments in the Western Indian Ocean - Sean Fennessy; Bernadine Everett; Fiona MacKay; Silvia Abdula; Jean Jacaques Be; Andrew Green; Chris Jenkins; Esther Fondo; Cang Hui; Amon Kimeli; Mary Kishe; Alex Mafuru; et al. (Western Indian Ocean Journal of Marine Science, 2025)
The Western Indian Ocean (WIO) hosts substantial marine biodiversity, which is better known from inshore and coastal hab- itats. The diversity from soft sediments of the shelf and slope is much less known regionally, which was the premise for the WIO-Benth Project. Existing seabed information and bottom trawl catch data were compiled for five countries (Kenya, Tanza- nia, Mozambique, South Africa, and Madagascar), to characterize seabed habitats and benthic (demersal trawl) communities of the continental shelf and upper slope in the western part of the WIO. Soft sediment (sand, mud) habitats were spatially dominant (54 %) relative to rock/mixed habitats; associated trawled fauna from these habitats were dominated by Chordata (fishes) and Arthropoda (mainly crustaceans). This overview of the special issue on the WIO-Benth Project provides a summary of the general results, greater details on which are provided in the issue’s constituent papers. In the process of compiling infor- mation and data from the region, the WIO-Benth Project has provided new knowledge to assist with marine spatial planning and decision-making in the WIO.

Overview of the WIO-Benth Project – benthic habitats and megafauna from soft sediments in the Western Indian Ocean - Sean Fennessy; Bernadine Everett; Fiona MacKay; Silvia Abdula; Jean Jacaques Be; Andrew Green; Chris Jenkins; Esther Fondo; Cang Hui; Amon Kimeli; Mary Kishe; Alex Mafuru; et al. (Western Indian Ocean Journal of Marine Science, 2025)
The Western Indian Ocean (WIO) hosts substantial marine biodiversity, which is better known from inshore and coastal hab- itats. The diversity from soft sediments of the shelf and slope is much less known regionally, which was the premise for the WIO-Benth Project. Existing seabed information and bottom trawl catch data were compiled for five countries (Kenya, Tanza- nia, Mozambique, South Africa, and Madagascar), to characterize seabed habitats and benthic (demersal trawl) communities of the continental shelf and upper slope in the western part of the WIO. Soft sediment (sand, mud) habitats were spatially dominant (54 %) relative to rock/mixed habitats; associated trawled fauna from these habitats were dominated by Chordata (fishes) and Arthropoda (mainly crustaceans). This overview of the special issue on the WIO-Benth Project provides a summary of the general results, greater details on which are provided in the issue’s constituent papers. In the process of compiling infor- mation and data from the region, the WIO-Benth Project has provided new knowledge to assist with marine spatial planning and decision-making in the WIO.

Variations in community perceptions of ecosystem services within the Tana River estuary, Kenya: Implications for ocean governance - Pascal Thoya; Margaret A. Owuor; Miriam Von Thenen; Johnstone O. Omukoto (Western Indian Ocean Journal of Marine Science, 2022)
Coastal communities in the Tana estuary, Kenya, rely on a variety of economic sectors linked to ecosystem services, including small-scale fisheries (SSF), commercial prawn fisheries, and tourism. Despite its environmental and social importance, the estuary has been negatively impacted by overexploitation, pollution, and climate change. As a result, developing integrated management approaches for this area is a priority. The integrated approach to ecosystem services (ES) evaluation has widespread support because it emphasizes people’s views of ecological value to human well-being and aims to provide a solution to the rapid depletion of our planet’s natural resources. This study applied mixed methods to understand the perspectives of the communities on ES. It was hypothesized that perceptions of ES differ across communities with different socioeconomic characteristics, and this hypothesis was tested in two communities (Ozi and Kipini) that share the same ecosystem but have different socioeconomic characteristics. Kipini is an area near the ocean, whereas Ozi is a rural area further upstream. Differences were noted in the valuation of cultural services, while there were similarities in provisioning and regulating services. Mangroves, other trees, and river systems were considered to have higher ES provision than the ocean, floodplains, and settlement areas. The Ozi community ranked the ocean higher than the Kipini community, even though Ozi was located further upstream from the ocean; consequently, the perception that communities benefit more from resources that they are close to could be false. The relevance of using social ES identification to determine the distribution of benefits from coastal ES is highlighted in this study and will be beneficial for informing decision-making and developing all-inclusive governance structures.

Policy gaps in the East African Blue economy: Perspectives of small-scale fishers on port development in Kenya and Tanzania - Pascal Thoya; Vera Horigue; Christian Möllmann; Joseph Maina; Kerstin S. Schiele (Frontiers in Marine Science, 2022)
Recently, the rights of small-scale fishers have increasingly been acknowledged in ocean governance because coastal development and various maritime activities have reduced traditional fishing grounds. More specifically, small-scale fisheries (SSF) are increasingly being threatened by ocean grabbing, pollution, and a lack of inclusiveness in decision-making processes. Although there are guidelines to resolve and reduce conflict, formal avenues to include fisher concerns, particularly in the context of ocean development and governance, remain a difficult task. Moreover, there is insufficient information on how fishers are impacted by coastal and marine development and how their concerns are included in the decision-making process. Hence, this study contributes to the SSF discourse by understanding and describing the characteristics and concerns of small-scale fishers from two coastal towns in East Africa with different levels of port development. Using data from perception surveys, focus group discussions, and participatory mapping, we discuss how fishers were involved in the decision-making processes to develop ports in Lamu, Kenya, and Bagamoyo, Tanzania. We found that fishers rely on nearshore ecosystems such as mangroves and coral reefs because of their accessibility since most fishers only use low-powered boats for fishing. Moreover, we found that the fishers’ livelihoods were severely affected by port development and that they were excluded from the decision-making process concerning the port’s construction and fishers’ compensations. While some fishers believe that new ports in the region can increase their livelihoods by creating new markets and jobs, this is unlikely to happen since most fishers are not qualified to work in formal port-related jobs. We propose three steps that will allow fishermen to participate in port development decision-making processes and contribute to the development of a sustainable SSF. These include improving engagement with fishers to allow meaningful participation in decision-making, developing a blue economy policy focused on SSF, and implementing maritime spatial planning.

Natural resource-use in the Lower Tana River Delta based on household surveys and remote sensing of land cover and land use patterns - Hamadi M. Mwamlavya; Cosmas N. Munga; Benard M. Fulanda; Johnstone O. Omukoto; Pascal Z. Thoya; Fiona Mackay; Fatma H. Manyenze; Johan C. Groeneveld (Western Indian Ocean Journal of Marine Science, 2021)
Household survey data and spatially explicit Sentinel-2 satellite images of land cover and land use during the dry and wet seasons were used to investigate livelihood strategies in the Lower Tana River Delta in Kenya, where food security and economic activity rely almost exclusively on ecosystem goods and services. Land cover classification of satellite imagery successfully showed seasonal changes to estuary-related vegetation and habitats from which land use cycles could be inferred. Flood-recession agriculture and part-time fishing were the most common activities at Ozi village, some 10 km upstream from the estuary mouth, whereas full-time fishing dominated activities at Kipini town, where the Tana Estuary discharges into Ungwana Bay. Seasonality of fishing at Kipini depended on favourable sea conditions, arrival of migrant fishers and peaks in shrimp abundance. Seasonality of agriculture at Ozi depended on the freshwater flooding regime, visible in satellite images as an inverse relationship of areas covered by wetlands and cultivated lands. The predominance of fishing assets at Kipini indicated specialization, which underlies a socio-economic network of fish processing, marketing, distribution and logistical support services. In contrast, mixed farming assets and traditional fishing gear at Ozi reflected more diversified farmer-fisher livelihoods, as a risk avoidance strategy. Key outcomes of this study were that land cover and land use were strongly seasonal, that coastal and upstream communities in the Tana Estuary relied on different combinations of ecosystem goods and services, and that livelihood strategies at the two locations differed fundamentally. Combining social, spatial and ecological data to describe socio-ecological systems typical of the Tana Estuary provided a broad platform for shared resource management strategies.

Satellite-derived bathymetry: A case study of Mombasa Port Channel and its approaches, Kenya - Amon Kimeli; Pascal Thoya; Noah Ngisiang’e; Harrison Ong’anda; Charles Magori (Western Indian Ocean Journal of Marine Science, 2018)